PSIKOEDUKASI KENALI EFIKASI DIRI: ENERGI BAGI MOTIVASI DAN POTENSI PADA SISWA SMA X - Fransisca Iriani Roesmala Dewi; Ruslinda Desiana Ginting (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
SMA X is a favorite school in Pekanbaru City, Riau. The conditions of favorite schools result in dif erences in theexperiences felt by students. There are students who have high self-ef icacy and there are also those who have lowself-ef icacy. Students with low self-ef icacy feel unsure of their ability to complete assignments and achieve desiredgoals. Intervention in the form of psychoeducation with the theme